Representación del conocimiento en datos Espacio-Temporales para SIGs: un enfoque basado en Esquemas Preconceptuales - Zapata Jaramillo, Carlos Mario (Editorial Bonaventuriana, 2018)
Geographic Information Systems (GIS) represent some geographic-dynamic phenomena and contain spatio-temporal data of geographical entities. Such data can be represented by using several diagrams: entity-relationship, object-oriented, and class diagrams. These diagrams have several ways to represent and store the spatio-temporal data, but they do not use the information contained on them for the improvement of the inter-diagram interoperability. In this paper we propose a spatiotemporal data representation. From such a representation, we can identify the minimal data to be used for promoting interoperability among several GIS communities. We use the so-called pre-conceptual schemas for representing knowledge in this subject. Pre-conceptual schemas allow exemplifying concepts and they are computationally manageable.